Psychometric validation of the Chinese version of the Adolescent Asthma Self-Efficacy Questionnaire - Wang, Yuanyuan; Chen, Hongyu; Cao, Jinjin; Li, Mei; Wang, Jianan; Jing, Ruochen (Frontiers in Psychology, 2022)
Background Self-efficacy was considered as a promising target for the self-management of symptoms for adolescents with asthma. The measurement of self-efficacy in adolescents with asthma requires effective self-report tools, which have not been met with at present. So, the aim of this study was to cross-culturally validate the Adolescent Asthma Self-Efficacy Questionnaire (AASEQ). Methods As many as 408 adolescents with asthma were invited to take up the psychometric properties test between July 2021 and June 2022. We conducted the confirmatory factor analysis (CFA) to determine the structure of the AASEQ. The relationship between the AASEQ and General Self-Efficacy Scale was tested to evaluate the construct validity. The reliability was evaluated by retest reliability, internal consistency, and interfactor correlation. Results The results of the present study showed that the confirmatory factor analysis indicated a significantly good fit for a four-factor model, which explained 62.697% of the total variance. The fit indices of the four-factor model were acceptable, and the standardized factor loading ranged from 0.631 to 0.880. The C-AASEQ showed an acceptable internal consistency (Cronbach's α = 0.810–0.927) and test-retest reliability (intraclass correlation coefficient = 0.64–0.89). Content validity index at the scale level was 0.96, and content validity index at the item level was 0.86 to 1. Conclusion The Chinese version of Adolescent Asthma Self-Efficacy Questionnaire showed consistently acceptable positive psychometric properties and can be used as an instrument to assess the self-efficacy of adolescents with asthma in China, as corroborated in the present study.